The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s13157-015-0704-9
|View full text |Cite
|
Sign up to set email alerts
|

Variation Among Genotypes and Source Habitats in Growth and Fecundity of the Wetland Invasive Plant Phalaris arundinacea L

Abstract: The spread of invasive wetland plants has resulted in a number of negative impacts to wetland habitats including reductions in biodiversity, displacement of native plants, and altered water flow. Phalaris arundinacea L. (Reed canarygrass) is a highly competitive invasive plant in North American wetlands. While research has focused on growth characteristics and competitive ability of P. arundinacea in wetland habitats, little is known about how its growth in upland conditions differs from that in wetlands. To c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Weedy and invasive species should be particularly useful for investigating patterns of morphological variation and adaptation at multiple spatial scales. Because many such species are geographically widespread and occur in a range of distinct habitats (e.g., Nelson & Anderson, ), they should experience a complicated mosaic of selection pressures. Many weedy and invasive species also harbor substantial genetic and/or phenotypic variability at the population level (Clements et al., ; Dlugosch & Parker, ; Lavergne & Molofsky, ; Vigueira, Olsen, & Caicedo, ; Warwick, Thompson, & Black, ), making it possible that spatial patterns of selection could yield corresponding patterns of phenotypic variation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weedy and invasive species should be particularly useful for investigating patterns of morphological variation and adaptation at multiple spatial scales. Because many such species are geographically widespread and occur in a range of distinct habitats (e.g., Nelson & Anderson, ), they should experience a complicated mosaic of selection pressures. Many weedy and invasive species also harbor substantial genetic and/or phenotypic variability at the population level (Clements et al., ; Dlugosch & Parker, ; Lavergne & Molofsky, ; Vigueira, Olsen, & Caicedo, ; Warwick, Thompson, & Black, ), making it possible that spatial patterns of selection could yield corresponding patterns of phenotypic variation.…”
Section: Introductionmentioning
confidence: 99%
“…Intraspecific trait variation is common in many species, reflecting processes such as local adaptation, phenotypic plasticity, and variable gene flow across the landscape (Albert, Grassein, Schurr, Vieilledent, & Violle, 2011). Particularly for species with large geographic distributions and ecological amplitudes, these processes may yield complex, non-neutral spatial patterns of intraspecific variation (Bhattarai et al, 2017;Nelson & Anderson, 2015). A large geographic range enhances the breadth of bioclimatic variation a species encounters, and selection in response to such spatially continuous variation should result in trait autocorrelation among nearby populations (Murray, Brown, & Grace, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the stable coexistence of P. arundinacea and P. australis in the Zhenjiang Waterfront Wetland must be the result of the combined effect of many factors, including the density effect of P. australis. In addition to the density effect of P. australis, many other obvious differences were observed between the two species, including the growth period, plant height, light compensation point, and root depth (Lavergne and Molofsky 2006;Zhang and Luo 2008;Fu et al 2011;Ge et al 2011;Nelson and Anderson 2015). In particular, Fu Weiguo suggested that despite the stronger competitiveness of P. australis compared with P. arundinacea, the latter's earlier germination of about 30 days resulting from the difference in growth period may have allowed this species to establish rapidly and preempt the establishment of P. australis, and the absence of shading by P. australis would also have been very beneficial for the early growth of P. arundinacea during this period Fu et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Nelson et al (2014) determined that the population genetic structure of wild, forage, and ornamental European and North American reed canarygrass harbored a high amount of genetic diversity within, as opposed to among, populations. Subsequent research has reconfirmed this in additional populations (Anderson et al, 2018;Nelson and Anderson, 2015). Thus, range expansion of P. arundinacea in North America is not a result of hybridization among European, forage, and North American individuals (Jakubowski et al, 2011) despite unsubstantiated theories to the contrary (Lavergne and Molofsky, 2007).…”
Section: Reed Canarygrass Biology and Historical Spreadmentioning
confidence: 92%